Workplace Inclusion of People With Health Issues, Immigrants, and Unemployed Youths—A Qualitative Study of Norwegian Leaders’ Experiences - Johnsen, Tone Langjordet; Fyhn, Tonje; Jordbru, Anika; Torp, Steffen; Tveito, Torill Helene; Øyeflaten, Irene (Frontiers in Psychology, 2022)
Aim: To explore leaders’ perceptions and experiences of facilitators and barriers for successful workplace inclusion of marginalized groups. Methods: Semi-structured individual interviews with 16 leaders who actively engaged in inclusion work, representing different occupations, were conducted. Systematic Text Condensation was used to structure the analysis. Results: The participating leaders emphasized that job match, including workers’ motivation, respect for workplace policies, and availability of appropriate accommodation, facilitated work inclusion. An active public support system providing professional and financial support to workers and leaders was also an important facilitator. Workers’ lack of motivation was highlighted as the most important barrier. Successful inclusion depended on all workers acknowledging responsibility for and contributing to an inclusive work environment. Being open and willing to discuss challenges, was an important part of making the inclusion work. In addition, leadership qualities such as empathy, patience, and a non-judgmental attitude appeared as a hallmark among these leaders who actively engaged in inclusion work. Conclusions: Workplace inclusion of marginalized groups was facilitated by job match, mutual respect, commitment and trust, as well as financial and practical support from the public support system. Leaders’ inclusion practices were furthermore affected by personal attitudes and perceptions of social responsibility. Even so, successful workplace inclusion was presented as a two-way street. Leaders have the main responsibility in initiating a respectful and trusting relationship, but both the worker and the leader needs to contribute to make the relationship thrive.